Chloromanganese and oxo-titanium (IV) phthalocyanines: Synthesis, electrochemistry and spectroelectrochemistry - BUDAK, ÖZLEM; KOCA, ATIF (My University, 2023)
Electrochemical properties of MPcs were determined with electrochemical and in-situ spectroelectrochemical measurements to investigate the influence of the metal center and the number and positions of the substituents. While H2Pc only illustrated Pc based redox processes, the incorporation of TiO2+ and Cl−1-Mn3+ cations into the cavity of Pc ring considerably altered the redox richness of the complexes. Two metal-based reduction couples were observed in addition to the Pc-based processes for both of TiOPc and MnPc. Moreover, altering the number and position of 4-(2-phenylpropan-2-yl)phenoxy substituents slightly influenced the basic redox activity of Pc ring and metal centers. All of these results supported the proposed structure of the complexes. During the redox reactions, pronounced spectral changes were observed with the in situ spectroelectrochemical measurements which caused distinct color changes. Rich redox responses and pronounced spectral and color changes of the complexes indicated their worth as functional material in various electrochemical technologies.
Keywords: Kimya; Fizikokimya; İnorganik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Inorganic Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; KİMYA, İNORGANİK VE NÜKLEER; KİMYA, FİZİKSEL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, PHYSICAL; MATERIALS SCIENCE, MULTIDISCIPLINARY; Fiziksel ve Teorik Kimya; Fizik Bilimleri; İnorganik kimya; Malzeme Kimyası; Physical and Theoretical Chemistry; Physical Sciences; Materials Chemistry; Electrochemistry; Manganese; Phthalocyanine; Spectroelectrochemistry; Titanium dioxide